RESOURCE-USE EFFICIENCY OF MILLET PRODUCTION UNDER SALINITY CONDITION IN NORTH SINAI GOVERNMENT, EGYPT - Dalia Abozaid; Sherien Mansour (Arab Universities Journal of Agricultural Sciences, 2016)
North Sinai farming community is facing many challenges such as increasing drought and salinity in water and soil, poor quality soils, a long hot summer with high solar radiation; in addition to poor experience of settled farmers and local Bedouins in improving traditional agriculture and animal productivity under saline conditions. The main objective of the study is to establish the efficiency of resource use in millet production among smallholder farmers in North Sinai region. Using a multi-stage random sampling procedure in selecting farmers interviewed. A structured questionnaire was administered to 60 smallholder farmers selected for analysis; the farmers were divided into two groups based on ownership and use of animals on the farm, and used a model to evaluate efficiency of the two groups. In this model, a Cobb-Douglas production function was fitted for the cross- sectional data generated from the survey. The ratio of marginal value product (MVP) to marginal factor cost (MFC) for all inputs was found to be greater than unity among all groups of farmers implying under-utilization of resources. Millet farmers were found to experience increasing returns to scale, meaning use of additional inputs in millet production would result in higher yields. The null hypothesis, which stated that smallholder farmers in North Sinai region are not allocating their farm resources efficiently in millet production, was tested and rejected at 5% level of significance. It was therefore concluded that millet farmers in North Sinai region were sub-optimally allocating resources in their production system.